PENGARUH SERVICESCAPE TERHADAP KEPUASAN KONSUMEN (Studi pada Penumpang Keberangkatan Domestik di Bandara Ahmad Yani Semarang) - Rijae, Zaki Muafa; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2018)
Ahmad Yani Airport Semarang is the airport that became one of the entrance to central java through air transportation. However, based on the information obtained there are complaints related to services at Ahmad Yani Airport Semarang such as a narrow parking lot, crowded waiting room and passenger accumulation during peak season This research aims to analyze the influence of servicescape dimensions named ambient conditions, spatial layout and functionality, signs, symbols and artifacts to customer satisfaction. Case study on domestic departures passengers at ahmad yani airport semarang.The number of sample used in this research were 100 respondents. Sample were chosen using quota sampling technique. The analytical method used in this research is Multiple Linear Regression Analysis where previously tested the validity and reliability, then performed classical assumption that includes Normality Test, Multicollinearity Test, and Heterokedastisitas Test with level of significance 5%.The result of this research found that ambient conditions, spatial layout and functionality and signs, symbols and artifacts positively significance influenced to customer satisfaction.